Dose-response effects of estrogenic mycotoxins (zearalenone, alpha- and beta-zearalenol) on motility, hyperactivation and the acrosome reaction of stallion sperm - Filannino, Angela (BioMed Central, 2011)
BACKGROUND: The aim of this study was to investigate the in vitro effects of the Fusarium fungus-derived mycotoxin, zearalenone and its derivatives alpha-zearalenol and beta-zearalenol on motility parameters and the acrosome reaction of stallion sperm. Since the toxic effects of zearalenone and its derivatives are thought to result from their structural similarity to 17beta-estradiol, 17beta-estradiol was used as a positive control for 'estrogen-like' effects. METHODS: Stallion spermatozoa were exposed in vitro to zearalenone, alpha-zearalenol, beta-zearalenol or 17beta-estradiol at concentrations ranging from 1 pM - 0.1 mM. After 2 hours exposure, motility parameters were evaluated by computer-assisted analysis, and acrosome integrity was examined by flow cytometry after staining with fluoroscein-conjugated peanut agglutinin. RESULTS: Mycotoxins affected sperm parameters only at the highest concentration tested (0.1 mM) after 2 hours exposure. In this respect, all of the compounds reduced the average path velocity, but only alpha-zearalenol reduced percentages of motile and progressively motile sperm. Induction of motility patterns consistent with hyperactivation was stimulated according to the following rank of potency: alpha-zearalenol >17beta-estradiol > zearalenone = beta-zearalenol. The hyperactivity-associated changes observed included reductions in straight-line velocity and linearity of movement, and an increase in the amplitude of lateral head displacement, while curvilinear velocity was unchanged. In addition, whereas alpha- and beta- zearalenol increased the percentages of live acrosome-reacted sperm, zearalenone and 17beta-estradiol had no apparent effect on acrosome status. In short, alpha-zearalenol inhibited normal sperm motility, but stimulated hyperactive motility in the remaining motile cells and simultaneously induced the acrosome reaction. Beta-zearalenol induced the acrosome reaction without altering motility. Conversely, zearalenone and 17beta-estradiol did not induce the acrosome reaction but induced hyperactive motility albeit to a different extent. CONCLUSIONS: Apparently, the mycotoxin zearalenone has 17beta-estradiol-like estrogenic activity that enables it to induce hyperactivated motility of equine sperm cells, whereas the zearalenol derivatives induce premature completion of the acrosome reaction and thereby adversely affect stallion sperm physiology. The alpha form of zearalenol still possessed the estrogenic ability to induce hyperactivated motility, whereas its beta stereo-isomere had lost this property.